Counseling guidance in improving family stability in facing a covid-19 pandemic - Rois Nafi'ul Umam (Journal of Advanced Guidance and Counseling, 2021)
Purpose – The purpose of this study is to provide a clear description of the issue of family stability during the pandemic and family counseling guidance as to the solution in improving family stability.Method – This study applied a descriptive qualitative approach with an interview as the technique to collect the data. The informants in this study were 5 people consisting of the executive board and the members of Al-Usroh family community in Balikpapan.Result - The result of the study shows that during the pandemic the issues influencing family stability are family financial crisis, boredom, and over anxiety. To improve family stability during the pandemic, family counseling guidance with a conjoint approach was carried out.Implication – This research might become a study on the application of family counseling guidance services to improve family stability.Originality – This study was about the effect of the covid-19 pandemic towards family stability and the role of family counseling guidance to improve family stability.***Purpose – Tujuan penelitian ini adalah untuk memberikan gambaran tentang masalah ketahanan keluarga di masa pandemi dan layanan bimbingan konseling keluarga sebagai solusi dalam meningkatkan ketahanan keluargaMethod – Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data wawancara. Informan dalam penelitian ini sebanyak 5 orang yakni dari pengurus dan anggota komunitas keluarga Al-Usroh BalikpapanResult  -  Hasil penelitian menunjukkan bahwa permasalahan di masa pandemi yang berpengaruh terhadap ketahanan keluarga seperti krisis finansial pada keluarga, kejenuhan dan kecemasan yang berlebihan. Dalam rangka meningkatkan ketahanan keluarga di masa pandemi ini, upaya yang dilakukan yakni melalui layanan bimbingan konseling kelompok dengan pendekatan conjoint.Implication – Penelitian ini dapat menjadi kajian tentang pemanfaatan layanan bimbingan konseling keluarga untuk meningkatkan ketahanan keluargaOriginality – Penelitian ini adalah penelitian tentang dampak pandemi covid-19 terhadap ketahanan keluarga dan peran bimbingan konseling keluarga untuk meningkatkan ketahanan keluarga